Investigating the consistency in countermovement jump performance after high-velocity and high-force PAPE: A multiday analysis - Stuart, A.; Vetrovsky, T.; Cochrane-Snyman, K. C.; Vieira, A.; Tufano, J. J. (The Journal of Strength and Conditioning Research, 2025)
Postactivation performance enhancement (PAPE) is widely acknowledged in both practical application and research. However, studies have primarily focused on single experimental PAPE sessions, neglecting the repeatability of protocols with the same individuals over time. The purpose of this study was to determine whether PAPE, involving high-velocity and high-force conditioning activities, could be observed at consistent time points across multiple sessions. Sixteen elite speed skaters (9 men: 23.1 ± 2.6 years and 7 women: 24.2 ± 4.7 years) participated in 6 sessions for each independent study. For all sessions, a standardized warm-up was performed, followed by 3 baseline bodyweight countermovement jumps (CMJ), and a potentiation protocol of 5 repeated band-assisted countermovement jumps at approximately 20% bodyweight reduction, or a single 5-second maximal effort isometric squat. Subsequently, subjects rested for 3, 5, and 7 minutes before performing a single bodyweight CMJ at each time point. Multiday analyses of variance showed mixed results for both protocols, with most effect sizes ranging from trivial to small. Linear mixed models indicated that at the individual level, subjects did not consistently jump higher at any specific post-PAPE rest time. The variance between baseline and post-PAPE jump height at the rest time that produced the greatest result was neither statistically significant nor statistically different (p > 0.05), compared with other rest times. Postactivation performance enhancement was identifiable across sessions but variability in jump performance and inconsistent effects made it difficult to observe repeatable responses within individuals over time, thus questioning the idea of "individualizing" PAPE in practice.